Structural, ferroelectric and optical properties of Bi2VO5.5 thin films deposited on platinized silicon {(100) Pt/TiO2/SiO2/Si} substrates - Kumari, N.; Krupanidhi, S.B.; Varma, K.B.R. (Applied physics. A, Materials science & processing, 2008)
Bismuth vanadate (Bi 2 VO 5.5 , BVO) thin films have been deposited by a pulsed laser ablation technique on platinized silicon substrates. The surface morphology of the BVO thin films has been studied by atomic force microscopy (AFM). The optical properties of the BVO thin films were investigated using spectroscopic ellipsometric measurements in the 300–820 nm wavelength range. The refractive index (n), extinction coefficient (k) and thickness of the BVO thin films have been obtained by fitting the ellipsometric experimental data in a four-phase model (air/BVO rough /BVO/Pt). The values of the optical constants n and k that were determined through multilayer analysis at 600 nm were 2.31 and 0.056, respectively. For fitting the ellipsometric data and to interpret the optical constants, the unknown dielectric function of the BVO films was constructed using a Lorentz model. The roughness of the films was modeled in the Brugmann effective medium approximation and the results were compared with the AFM observations.